The intercultural approach in Beca 18. The case of bilingual students in an institute of higher education in Lima-Peru - Anselmo Vargas, José Luis (2021)
Based on the perception of the students, this study analyzes whether the Beca 18 Program implements the approach and application of an intercultural educational experience in the development of the career of its scholarship holders. It also analyzes whether the tutoring area of the Institute develops a socioemotional and academic accompaniment by applying activities that revalue the intercultural component of its scholarship holders. The methodology used was qualitative, with an interpretative design. The population for this study were the students of the Beca 18 program of the International Business Administration career of the CERTUS Institute.A representative sample was not contemplated; the use of the questionnaire to carry out the semi-structured interviews was evaluated.Among the conclusions, it was found that the Beca 18 program does not contemplate in the design of its tutoring guidelines, a sociocultural and intercultural strategy for scholarship holders who migrate to the capital to integrate into a different culture. Likewise, the Institute does not develop an intercultural educational strategy for its scholarship holders through the development of culturally relevant content. It was also concluded that despite the cultural diversity of the scholarship holders, the Institute's tutoring area does not develop activities that identify, value and disseminate interculturality, because this would mean including it in the programming and giving it specialized treatment.